Analisis Kontribusi Retribusi Pelayanan Parkir di Tepi Jalanan Umum Terhadap Pendapatan Asli Kabupaten Bone - Mila Juliana; Asmirani Asmirani (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study discusses the estimation of district parking payments for regional income in Bone Regency in 2012-2016. This research is intended to find out (1) the average level of regional income from allowance funds in Bone District 2012-2016, (2) the marginal level of regional original income from parking fees on the side of the public road Bone District 2012-2016. The results showed that parking fees at the edge of public roads contributed significantly to local revenue only in 2013 because of APAD MPAD, while parking fees at the edge of public roads did not contribute significantly to local revenues in 2012, 2014, 2015 and 2016 due to APAD MPAD.